Effect of annular focusing of ultrasound on rate of stone erosion using cavitation bubbles. (21st June 2018) - Yura, Toshiya; Lafond, Maxime; Yoshizawa, Shin; Umemura, Shin-Ichiro
Abstract: Shock wave lithotripsy has been one of the first-line treatments to fragment kidney stones. One disadvantage of this method is that some residual stone fragments can be too large to pass through the ureters. Stone fragments can be made small enough by ultrasonically induced cavitation erosion, but the erosion rate, with conventional single-spot focusing, tends to be low owing to ultrasound attenuation by excessively generated cavitation bubbles upstream of the stone surface. Sector vortex annular focusing can generate cavitation bubbles widely and thinly. We propose exposure sequences utilizing this focusing scheme and investigated their effect on erosion rate using a stone model. Sector vortex annular focusing showed an erosion rate significantly higher than that of single-spot focusing. Among them, switching between the two focusing schemes provided the highest rate, higher than the mathematical sum of those of the two schemes, and even higher than that of sector vortex focusing at the same pulse repetition.